Isolation and characterization of novel glycoproteins from fish epidermal mucus : correlation between their pore-forming properties and their antibacterial activities - Ebran, Nathalie; Julien, Sylviane; Orange, Nicole; Aupérin, Benoît; Molle, Gérard (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2000)
International audience In fish, a layer of mucus covers the external body surface contributing therefore, among other important biological functions, to the defense system of fish. The prevention of colonization by aquatic parasites, bacteria and fungi is mediated both by immune system compounds (IgM, lysozyme, etc.) and by antibacterial peptides and polypeptides. We have recently shown that only the hydrophobic components of crude epidermal mucus of fresh water and sea water fish exhibit strong pore-forming properties, which were well correlated with antibacterial activity [N. Ebran, S. Julien, N. Orange, P. Saglio, C. Lemaitre, G. Molle, Comp. Biochem. Physiol. 122 (1999)]. Here, we have isolated novel glycosylated proteins from the hydrophobic supernatant of tench (Tinca tinca), eel (Anguilla anguilla) and rainbow trout (Oncorhynchus mykiss) mucus. The study of their secondary structure was performed by circular dichroism and revealed structures in random coil and α-helix in the same proportions. When reconstituted in planar lipid bilayer, they induced the formation of ion channels. This pore-forming activity was well correlated with a strong antibacterial activity (minimal inhibitory concentration<1 μM for the three proteins) against both Gram-negative and Gram-positive bacteria. Our results suggest that fish secrete antibacterial glycoproteins able to kill bacteria by forming large pores (several hundreds to thousands of pS) in the target membrane.